O saber-fazer de educadores diante da violência na escola - Pablo Henrique Teodoro de Lima (2022)
This work is the result of a research whose main objective was to analyze what know-how educators present when dealing with cases of violence at school. Having as a trigger the increasing levels of violence that school institutions face, as well as the difficulty that many educators (teachers, coordinators and principals) face when dealing with the most enigmatic cases of violence at school, we seek to understand them what unique know-how they invent to conduct their work with the unpredictability that the teaching profession presents to them. Resorting to pedagogical knowledge, but also to psychoanalysis, as guides for our reflections, and taking for granted that the unique form does not exist, leaving us on a case-by-case basis, we had as secondary objectives: to know what Basic Education educators understand as violence at school, its sources and what possible projects they develop to deal with it; as well as to investigate, from the perspective of the psychoanalytic concept of know-how, what other knowledge can be produced by doing not designed or not planned by these same educators. Considering that this is a research with subjects, the offer of the word proved to be of fundamental importance. For this, we used the in-depth interview, so that they could talk freely about the proposed topic, letting their know-how emerge. The analysis of the interviews was carried out from the clinical analysis of discourse, a tool that made possible to infer something unique in the know-how of educators when dealing with cases of violence at school. In order to build and support our research object, we cross-referenced data from four main sources, namely: statistical reports from the Belo Horizonte City Hall about violence in schools; Detailed Occurrence Bulletins of the Municipal Civil Guard; literature review and theoretical foundation on violence and teaching know-how; beyond listening to the subjects. We found the relevance of considering the uniqueness and inventiveness of each educator's teaching know-how, subjectivized throughout their teaching career.